Finite element analysis of connecting rod failure - Chow, Xiang Hui (Nanyang Technological University, 2021)
This study investigates connecting rods' performance under different conditions using the finite element analysis method through ANSYS. Total two general conditions were simulated. Firstly, the connecting rod's performance under different materials is aluminium alloy, titanium alloy, and stainless steel. Secondly, design modifications were made to titanium alloy connecting rod. Von misses stress, deformation, life, and safety factor were obtained from the simulation result. The basic knowledge of finite element analysis and ANSYS acquired through this project will lay the foundation for future simulation work.